A Model for Safe Delivery Based on Clinical Governance - Afsaneh Keramat; Forozun Olfati; Saeed Asefzadeh; Nasrin Changizi; Masoud yunesian (Tehran University of Medical Sciences, 2017)
Background: Because of the current population policies adopted in Iran followed by increasing the number of births, this study aimed to investigate the current situation of safe delivery and proposed a model based on clinical governance. Materials and Methods: This study is a combinatorial-exploratory research (Mixed Method) conducted in four hospitals in Qazvin and Semnan provinces including two stages in 2014.  The first stage was the assessment of current situation; clarifying safe delivery, reviewing literatures, providing two checklists, assessment of current situation based on assessment of continuous quality improvement and assurance of the quality and the second stage was presenting the model including codification of safe delivery model in seven axes of clinical governance, the approval of the model on the panel using nominal group technique. Results: In quality assurance, hospital (4) and hospital (2) obtained the maximum score (1431) and minimum score (1237) respectively. All hospitals in continuous quality assessment, admission in the intensive care unit (P < 0.001), mothers with severe consequence of pregnancy (P = 0.004) and 16 cases out of 27 errors had significant statistical difference. Conclusions: In order to improve the quality of Maternity ward, hospitalschr('39') accreditation also should be based on the principles of clinical governance. In addition to evaluations based on quality assurance and annual accreditation, assessment using continuous quality improvement methods based on clinical governance is essential. The proposed model includes seven axes of clinical governance.